Adsorption of Hydrocarbons Using Natural Adsorbents of Plant Origin; Procedia Chemistry; Vol. 15 : Chemistry and Chemical Engineering in XXI century (CCE 2015) - Rotar O. V. Olga Vasilievna; Rotar V. G. Viktor Grigoryevich; Iskrizhitsky A. Alexander; Sharipov Z. Zinnur; Pimenova A. Alexandra (2015, 2015)
Title screen